PERAN KEARIFAN LOKAL DALAM KONSERVASI SATWA LIAR ENDEMIK DI HUTAN TROPIS INDONESIA - Wilma Imlabla; John F. Sahusilawane (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
Indonesia boasts abundant biodiversity, especially unique wildlife in tropical forests that encounter numerous threats. This research seeks to examine the function of local knowledge in preserving native wildlife by utilizing qualitative methods and conducting detailed interviews with 10 informants. The results indicate that local knowledge, including traditional restrictions, ceremonies, and community oversight, is vital for the conservation of wildlife. Contemporary modernization issues and financial strains are key dangers, yet cooperation among stakeholders improves conservation success. Passing cultural values to younger generations is crucial for sustainability. This research highlights the significance of acknowledging local knowledge in conservation strategies for sustainable ecosystems. The findings can act as a guideline for formulating participatory conservation policies in Indonesia.